Comparison of antifungal activity of medicinal plant Tylophora indica Merr. with its in vitro raised plant and callus - Razia Khatoon & , Noor Jahan & , Anwar Shahzad, Mohammad Shahid (Journal of Applied Pharmaceutical Science, 2013)
Article titled ‘Comparison of antifungal activity of medicinal plant Tylophora indica Merr. with its in vitro raised plant and callus’ published in Journal of Applied Pharmaceutical Science, Volume: 3, Issue: 8, August, 2013, is being retracted. It has been reported that the large part of the text appeared in this article was plagiarized from a previously published article (Jahan et al., 2013). Thus, we retract this article from the literature according to the guidelines of Committee on Publication Ethics (Wager et al., 2009).